Maintaining healthy eating behaviour: experiences and perceptions of young adults - Allom, V.; Mullan, Barbara (Emerald Group Publishing Ltd., 2014)
Purpose – The prevalence of overweight and obesity is increasing, particularly in young adults who recently have been shown to experience more weight gain than other demographics. Research has focused on factors leading to this weight gain, implicating the abundance of unhealthy foods in the direct environment, yet limited research has examined why some individuals are able to successfully regulate their eating behaviour in this “food-rich environment”. The aim of this research was to explore the perceptions and experiences of successful healthy eaters in order to determine factors that distinguish this group from unhealthy eaters. Design/methodology/approach – Thirty-five healthy weight young adults, who considered themselves to be healthy eaters, participated in seven semi-structured focus groups. Key questions examined how these individuals regulated their eating behaviour and their perceptions regarding such self-control processes. Findings – Thematic analysis revealed that individuals who are successful at maintaining healthy eating behaviour perceive the same barriers as non-successful individuals, yet are able to employ self-control techniques to overcome these barriers. Additionally, continually exerting self-control appeared to facilitate the formation of healthy eating habits. Research limitations/implications – Future research may benefit from attempting to modify self-control ability and develop healthy habits. Originality/value – While factors leading to obesity and the cognitions of those who are overweight have been extensively examined, limited research has focused on those who are able to regulate their eating behaviour. Additionally, limited qualitative research has examined implicit theories of self-control in an eating context.